Sex ratios and crime: evidence from China's one-child policy - Lena Edlund; Hongbin Li; Junjian Yi; Junsen Zhang (Institute for the Study of Labor (IZA), 2007)
Sex ratios (males to females) rose markedly in China in the last two decades, and crime rates nearly doubled. This paper examines whether the two are causally linked. High sex ratios imply fewer married men, and marriage has been conjectured to be a socializing force. Our paper exploits the quasi-natural experiment generated by the Chinese one-child policy, a policy which is widely held to be behind the surplus of sons. While a national policy, its implementation was local. We show that the provincial level implementation was unrelated to contemporaneous economic characteristics of the province. Instead, individual characteristics of the provincial party secretary influenced the timing. Moreover, leaders were systematically rotated such that 10 years on, leader characteristics were serially uncorrelated. Using annual province-level data for the period 1988-2004, we show that a 0.01 increase in the sex ratio raised violent and property crime rates by some 3%, suggesting that the rise in excess males may account for up to one-seventh of the overall rise in crime.
Keywords: J12; 330; Male-biased sex ratios; crime; one-child policy; China; Kriminalität; Familienplanung; Bevölkerungsstruktur; Geschlecht; China